Worst to first : the true story of Z100 New York [videorecording (DVD)] - Shannon, Scott; Duran, Elvis, 1964-; Bon Jovi, Jon; Jett, Joan (Kino Lorber, 2022)
The true story of the legendary Z100 New York radio station following the colorful characters that started the station in the early '80s, and how they used unconventional and outlandish methods to go from New York City's worst-rated radio station to number one.